Optimized aberration correction for sonar arrays - Kirkebo, Jan Egil; Austeng, Andreas (Global Oceans 2020: Singapore – U.S. Gulf Coast, 2020)
In this paper a method using simulated annealing is applied to the problem of array pattern synthesis subject to aberrations. For linear arrays an optimal suppression of the maximum sidelobe level can be achieved using a Dolph-Chebyshev window. However, the sensitivity of this window to position and phase aberrations means it has practical limitations for use with sonar arrays. Instead, more robust windows such as Hamming or Hanning windows are used, with a reasonable trade-off between robustness, mainlobe width and sidelobe levels. Two important questions are: 1) What is the optimal window function to use for linear arrays when facing the problem of aberrations? 2) How can proper window functions be found for more complex geometries? We use a computationally efficient and iterative optimization technique to answer these questions, in order to find the optimal window for any array geometry subject to aberrations. Applied to a linear array, it shows that the best solution is approximately a Hanning window. The method is then applied to a cylindrical sonar array, similar to those used in commercial fishery applications. Compared to a uniformly weighted array, the resulting beampattern has reduced flat "Dolph-Chebyshev" -like sidelobe levels, with only a slight increase in the mainlobe width.